Resin composition, cured film, method for producing a pattern of the cured film, and electronic component

The resin composition, featuring a polyimide precursor with specific acid anhydride and alicyclic diamine residues, addresses the challenges of adhesion, stability, and water absorption in semiconductor device films, offering improved curability and mechanical properties.

JP7666026B2Active Publication Date: 2025-04-22TORAY INDUSTRIES INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021036045
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-08
Publication Date
2025-04-22
Estimated Expiration
2041-03-08

AI Technical Summary

Technical Problem

Existing photosensitive resin compositions for surface protection films and interlayer insulating films in semiconductor devices face challenges such as insufficient adhesion strength to copper, poor storage stability, low elongation and strength, and high water absorption.

Method used

A resin composition containing a polyimide precursor with a residue of an acid anhydride and an alicyclic diamine residue, which imparts low temperature curability, high elongation, and low water absorption properties, along with a solvent to enhance processability.

Benefits of technology

The resin composition achieves excellent room temperature storage stability, low temperature curability, high elongation, high strength, and low water absorption, making it suitable for use in semiconductor devices that require high film properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666026000022
    Figure 0007666026000022
  • Figure 0007666026000023
    Figure 0007666026000023
  • Figure 0007666026000024
    Figure 0007666026000024
Patent Text Reader

Abstract

To provide a resin composition that can be cured at a low temperature of 250°C or less, has excellent room temperature storage stability, has low water absorption even in a high humidity environment when used as a cured film, and has high elongation and high strength.SOLUTION: Provided is a resin composition containing (A) a polyimide precursor and a solvent (B), and in which the (A) polyimide precursor has a specific acid anhydride residue and has a specific alicyclic diamine residue.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and more particularly to a photosensitive resin composition suitable for use in a surface protective film or interlayer insulating film for electronic components such as semiconductor elements, an insulating layer for organic electroluminescent elements, and the like. [Background technology]

[0002] Conventionally, polyimide resins and polybenzoxazole resins, which have excellent heat resistance and mechanical properties, have been widely used for surface protection films and interlayer insulation films of semiconductor elements of electronic components. Usually, polyimide resins and polybenzoxazole resins are obtained by thermally dehydrating and cyclizing the coating film of their precursors to obtain thin films with excellent heat resistance and mechanical properties. In this case, high-temperature baking at about 350°C is usually required. However, for example, MRAM (Magnetoresistive Random Access Memory), which is promising as a next-generation memory, and sealing resins are weak against high temperatures. Therefore, in order to use them for surface protection films of such elements and interlayer insulation films of fan-out wafer-level packages that form rewiring structures on sealing resins, polyimide resins or polybenzoxazole resins that can be hardened by baking at a low temperature of about 250°C or less and can obtain high film properties such as heat resistance and mechanical properties that are comparable to conventional materials baked at a high temperature of about 350°C are required. In addition, in recent years, semiconductor packages have been finer in wiring due to the demand for high integration, miniaturization, and high speed. Therefore, there is a demand for insulating materials with low water absorption to have crack resistance against the stress that accompanies multi-layering, as well as to suppress changes in parasitic components (resistance, capacitance, etc.) and defects during the reflow process.

[0003] Surface protective films and interlayer insulating films of semiconductor elements of electronic components require the formation of through holes. One of the methods for forming the through holes is etching using a positive photoresist. However, this method requires the steps of applying and peeling off the photoresist, which is problematic in that it is cumbersome. Therefore, heat-resistant materials imparted with photosensitivity have been studied for the purpose of streamlining the work process. When using a resin cured film formed from a photosensitive resin composition imparted with photosensitivity, additives such as a photosensitizer, a sensitizer, an acid generator, and a dissolution regulator that constitute the composition remain in the cured film even after heat curing, so that the adhesive strength with the base metal is lower, the curing temperature is higher, and the dielectric constant is higher than that of a film that does not contain additives. To address these issues, a photosensitive resin composition that suppresses copper corrosion by adding a copper discoloration inhibitor to the photosensitive resin (see Patent Document 1), a photosensitive resin composition that combines low-temperature curing and photosensitivity due to a photobase generator, and other technologies have been disclosed (see Patent Document 2).

[0004] Besides photosensitive resin compositions, a study on processing polyimide with a laser without using a photosensitizer has also been reported (see Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-169980 A [Patent Document 2] JP 2011-213783 A [Patent Document 3] JP 2001-213962 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the photosensitive resin composition described in Patent Document 1, which contains a copper discoloration inhibitor, does not have sufficient adhesion strength to copper, and the photosensitive resin composition described in Patent Document 2, which contains a photobase generator, has good physical properties but poor storage stability. The polyimide for laser processing described in Patent Document 3 has low elongation and strength, and is insufficiently imidized at low temperatures. In addition, all of these have high water absorption properties that are characteristic of polyimides. [Means for solving the problem]

[0007] In order to solve the above problems, the present invention relates to the following. The present invention comprises a polyimide precursor (A) having an acid anhydride residue represented by formula (1) and an alicyclic diamine residue, and a solvent (B), The alicyclic diamine residue has one or more structures selected from the group consisting of formula (2), formula (3), and formula (4).

[0008] [ka]

[0009] In formula (1), X 1 and X 2 represents an oxygen atom, a sulfur atom, or an -NH- group, and n represents an integer of 4 to 20.

[0010] [ka]

[0011] In formula (2), the * symbol indicates a bond.

[0012] [ka]

[0013] In formula (3), R 1 and R 2each independently represents a hydrogen atom, a methyl group, or a trifluoromethyl group, and m represents an integer in the range of 1 to 10. The * symbol represents a bond.

[0014] [ka]

[0015] In formula (4), R 3 and R 4 each independently represents a hydrogen atom, a methyl group, or a trifluoromethyl group, and the * symbol represents a bond. Effect of the Invention

[0016] The resin composition of the present invention has excellent room temperature storage stability and low temperature curing property. In addition, the cured film obtained by curing the composition has high elongation, high strength, and low water absorption. [Brief description of the drawings]

[0017] [Figure 1] 1 is an enlarged cross-sectional view of a pad portion of a semiconductor device having bumps; [Diagram 2] 1A to 1C are diagrams illustrating a detailed method for manufacturing a semiconductor device having bumps. [Diagram 3] 1 is an enlarged cross-sectional view of a pad portion of a semiconductor device according to an embodiment of the present invention; [Figure 4] 1 is a cross-sectional view of a coil component of an inductor device showing an embodiment of the present invention. [Diagram 5] 1 is a schematic diagram of a coplanar feed type microstrip antenna, which is a type of planar antenna. [Figure 6] 1 is a schematic diagram showing a cross section of a semiconductor package including an IC chip (semiconductor element), rewiring, a sealing resin, and an antenna element. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The present invention relates to a polyimide precursor (A) having an acid anhydride residue represented by formula (1) and an alicyclic diamine residue, and a solvent (B), The alicyclic diamine residue is a resin composition having one or more structures selected from the group consisting of formula (2), formula (3), and formula (4).

[0019] [ka]

[0020] In the formula, X 1 and X 2 represents an oxygen atom, a sulfur atom, or an --NH-- group, and n represents an integer of 4 to 20.

[0021] [ka]

[0022] In formula (2), the * symbol indicates a bond.

[0023] [ka]

[0024] In formula (3), R 1 and R 2 each independently represents a hydrogen atom, a methyl group or a trifluoromethyl group, m represents an integer within the range of 1 to 10, and the * symbol represents a bond.

[0025] [ka]

[0026] In formula (4), R 3 and R 4 each independently represents a hydrogen atom, a methyl group or a trifluoromethyl group, and the * symbol represents a bond. Each component will be described below.

[0027] The polyimide precursor (A) (hereinafter sometimes referred to as component (A)) contains a residue of an acid anhydride represented by formula (1). Since component (A) contains a residue of an acid anhydride represented by formula (1), the resin composition can be imidized at a low temperature of 250°C or less without using an imidization accelerator such as a base generator when curing the resin composition. The imidization makes the resin insoluble in various solvents and cures the resin composition. In addition, the cured film obtained by curing the resin composition has high elongation and strength, and is excellent in processability with a UV laser.

[0028] [ka]

[0029] In formula (1), X 1 and X 2 represents an oxygen atom, a sulfur atom, or an -NH- group. Among these, from the viewpoint of the solubility of the component (A) in a solvent, X 1 and X 2 are preferably oxygen atoms. In formula (1), n ​​represents an integer of 4 to 20. Of these, n is preferably 8 to 16 from the viewpoint of a balance between low-temperature curing property, moisture absorption, and heat resistance. When n is less than 4, it is difficult to obtain the effect of promoting imidization at low temperatures, and when n is 21 or more, there is a concern of a decrease in the glass transition point. Here, when the symbol "to" is used in the present invention, it means that the upper and lower limit numbers are included unless otherwise specified.

[0030] The polyimide precursor (A) preferably contains 30 mol % or more and 100 mol % or less of the acid anhydride residue represented by the formula (1) relative to 100 mol % of the total carboxylic acid residues in the polyimide precursor (A). By setting the content within the above range, the curing temperature can be lowered. There is no particular upper limit, but by keeping the content at 70 mol % or less, different properties can be imparted depending on the other monomers, and when the content is 50 mol % or less, the balance with other properties is even better, which is more preferable.

[0031] Examples of the acid anhydride represented by the formula (1) include tetramethylene bistrimellitate dianhydride, pentamethylene bistrimellitate dianhydride, hexamethylene bistrimellitate dianhydride, heptamethylene bistrimellitate dianhydride, octamethylene bistrimellitate dianhydride, nonamethylene bistrimellitate dianhydride, decamethylene bistrimellitate dianhydride, dodecamethylene bistrimellitate dianhydride, tetradecamethylene bistrimellitate dianhydride, hexadecane Ester compounds such as camethylene bistrimellitate dianhydride and octadecamethylene bistrimellitate dianhydride, as well as tetraethylene bistrimellitate amide dianhydride, pentamethylene bistrimellitate amide dianhydride, hexamethylene bistrimellitate amide dianhydride, heptamethylene bistrimellitate amide dianhydride, octamethylene bistrimellitate amide dianhydride, nonamethylene bistrimellitate amide dianhydride, decamethylene bistrimellitate amide dianhydride, Examples of the amide compounds include water, dodecamethylene bistrimellitic acid amide dianhydride, tetradecamethylene bistrimellitic acid amide dianhydride, hexadecamethylene bistrimellitic acid amide dianhydride, and octadecamethylene bistrimellitic acid amide dianhydride, as well as thioester compounds such as tetraethylene bistrimellitic acid thioester dianhydride, pentamethylene bistrimellitic acid thioester dianhydride, hexamethylene bistrimellitic acid thioester dianhydride, heptamethylene bistrimellitic acid thioester dianhydride, octamethylene bistrimellitic acid thioester dianhydride, nonamethylene bistrimellitic acid thioester dianhydride, decamethylene bistrimellitic acid thioester dianhydride, dodecamethylene bistrimellitic acid thioester dianhydride, tetradecamethylene bistrimellitic acid thioester dianhydride, hexadecamethylene bistrimellitic acid thioester dianhydride, and octadecamethylene bistrimellitic acid thioester dianhydride. From the viewpoint of a balance between low-temperature curing property, moisture absorption, solvent solubility, and heat resistance, examples of the usable polyimide include octamethylene bistrimellitate dianhydride, nonamethylene bistrimellitate dianhydride, decamethylene bistrimellitate dianhydride, and dodecamethylene bistrimellitate dianhydride.The above-mentioned acid anhydrides can be used alone or in combination of two or more. These tetracarboxylic dianhydrides can be synthesized from trimellitic anhydride monochloride and the corresponding diol.

[0032] The component (A) further contains an alicyclic diamine residue. The alicyclic diamine residue has one or more structures selected from the group consisting of formula (2), formula (3), and formula (4). The presence of such a residue reduces water absorption, and the moisture absorption rate under constant temperature and humidity conditions (e.g., 23°C / 45% RH) can be reduced. In addition, the residue also plays a role in supporting the imidization of the acid anhydride residue represented by formula (1) at low temperatures.

[0033] [ka]

[0034] In formula (2), the * symbol indicates a bond. Examples of alicyclic diamines having a structure represented by formula (2) include trans-1,4-cyclohexanediamine, trans-1,3-cyclohexanediamine, trans-1,2-cyclohexanediamine, cis-1,4-cyclohexanediamine, cis-1,3-cyclohexanediamine, cis-1,2-cyclohexanediamine, 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, and 1,4-bis(aminomethyl)cyclohexane. Among these, trans-1,4-cyclohexanediamine is preferred because it has a small thermal expansion.

[0035] [ka]

[0036] In formula (3), R 1 and R 2 each independently represents a hydrogen atom, a methyl group, or a trifluoromethyl group, and m represents an integer in the range of 1 to 10. The * symbol represents a bond. Examples of alicyclic diamines having a structure represented by formula (3) include 4,4'-methylenebis(cyclohexylamine), 4,4'-methylenebis(2-methylcyclohexylamine), 4,4'-isopropylidenebis(cyclohexylamine), 4,4'-isopropylidenebis(2-methylcyclohexylamine), 4,4'-hexafluoroisopropylidenebis(cyclohexylamine), and 4,4'-hexafluoroisopropylidenebis(2-methylcyclohexylamine).

[0037] [ka]

[0038] In formula (4), R 3 and R 4 each independently represents a hydrogen atom, a methyl group, or a trifluoromethyl group, and the * symbol represents a bond. Examples of the alicyclic diamine having the structure represented by formula (4) include 4,4'-bicyclohexyldiamine, 2,2'-methyl-4,4'-aminobicyclohexane, and 2,2'-trifluoromethyl-4,4'-aminobicyclohexane.

[0039] In the present invention, the component (A) is preferably a resin structure having a structure represented by the following formula (5).

[0040] [ka]

[0041] In formula (5), multiple R 5 Each independently represents a tetravalent to hexavalent organic group having 4 to 40 carbon atoms. 6 each independently represents a divalent organic group having 2 to 40 carbon atoms; R 7 represents a hydrogen atom or an organic group having 1 to 20 carbon atoms.

[0042] The component (A) may contain an acid anhydride residue other than the acid anhydride residue represented by the formula (1). Among these, from the viewpoint of processability with a UV laser, it is preferable that the compound contains an aromatic acid dianhydride residue, and it is more preferable that the compound contains a biphenyltetracarboxylic acid dianhydride residue or a derivative residue thereof.

[0043] Specific examples include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2, 3-dicarboxyphenyl)propane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, 1,2,5,6-naphthalenetetracarbonate carboxylic dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 9,9-bis{4-(3,4-dicarboxyphenoxy)phenyl}fluorene dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 2,3,5,6-pyridinetetracarboxylic dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,2,3,4-cyclobutenetetracarboxylic dianhydride, 1,2,3,4-Cyclopentanetetracarboxylic dianhydride, 1,2,4,5-Cyclohexanetetracarboxylic dianhydride, 3,4-Dicarboxy-1,2,3,4-tetrahydro-1-naphthalenesuccinic dianhydride, 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic dianhydride, 2,3,5-tricarboxy-2-cyclopentaneacetic dianhydride, bicyclo[2.2.2] Oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 2,3,4,5-tetrahydrofuran tetracarboxylic dianhydride, 3,5,6-tricarboxy-2-norbornane acetic dianhydride, 1,3,3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione, and acid dianhydrides having the structure shown in the formula below, as well as compounds in which some of the hydrogen atoms of these aromatic rings or hydrocarbons are substituted with alkyl groups having 1 to 10 carbon atoms, etc., can be mentioned, but are not limited to these. These can be used alone or in combination of two or more.

[0044] [ka]

[0045] [ka]

[0046] In the above structure, R 8 represents an oxygen atom, C(CH3)2 or SO2, R 9 ~R 12 represents a hydrogen atom, a hydroxyl group, or a thiol group.

[0047] The component (A) may contain a diamine residue other than the alicyclic diamine residues having the structures represented by the formulas (2) to (4). For example, the inclusion of a dimethylsiloxane structure or a diphenyl ether structure can impart high elongation, and the inclusion of a biphenyl group improves UV ablation properties. Other examples include the introduction of a phenolic hydroxyl group to impart alkali solubility, and the introduction of polycyclic aromatic groups or heavy elements to increase the refractive index.

[0048] Specific examples include 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl methane, 4,4'-diaminodiphenyl methane, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 1,4-bis(4-aminophenoxy)benzene, m-phenylenediamine, p-phenylenediamine, 1,5-naphthalenediamine, 2,6-naphthalenediamine, ... bis(4-aminophenoxyphenyl)sulfone, bis(3-aminophenoxyphenyl)sulfone, bis(4-aminophenoxy)biphenyl, bis{4-(4-aminophenoxy)phenyl}ether, 1,4-bis(4-aminophenoxy)benzene, benzidine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-diethyl-4,4'-diaminobiphenyl, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, 3,3 '-Ditrifluoromethyl-4,4'-diaminobiphenyl, 2,2',3,3'-tetramethyl-4,4'-diaminobiphenyl, 3,3',4,4'-tetramethyl-4,4'-diaminobiphenyl, bis(3-amino-4-hydroxyphenyl)sulfone, bis(3-amino-4-hydroxyphenyl)propane, bis(3-amino-4-hydroxyphenyl)methylene, bis(3-amino-4-hydroxyphenyl)ether, bis(3-amino-4-hydroxy)biphenyl, bis(3-amino-4-hydroxyphenyl)fluorene, etc. Any aromatic diamines, such as bis(3-aminopropyl)tetramethyldisiloxane, bis(p-aminophenyl)octamethylpentasiloxane, ethylenediamine, 1,3-diaminopropane, 2-methyl-1,3-propanediamine, 1,4-diaminobutane, 1,5-diaminopentane, 2-methyl-1,5-diaminopentane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, 1,11-diaminoundecane, 1,12-diaminododecane, 1,Examples of the diamine include aliphatic diamines such as 2-bis(2-aminoethoxy)ethane, KH-511, ED-600, ED-900, ED-2003, EDR-148, EDR-176, D-200, D-400, D-2000, THF-100, THF-140, THF-170, RE-600, RE-900, RE-2000, RP-405, RP-409, RP-2005, RP-2009, RT-1000, HE-1000, HT-1100, and HT-1700 (all trade names, manufactured by HUNTSMAN Co., Ltd.), and compounds in which a portion of the hydrogen atoms of these aromatic rings or hydrocarbons are substituted with alkyl groups having 1 to 10 carbon atoms, but are not limited to these. The other diamines to be copolymerized can be used as they are or as the corresponding diisocyanate compounds or trimethylsilylated diamines. Two or more of these diamine components may also be used in combination.

[0049] The component (A) preferably has a biphenyl structure. The biphenyl structure provides a high strength and high elongation cured film and improves ablation processability with UV laser. Methods for introducing the biphenyl structure include using an acid component and / or a diamine component having a biphenyl structure as a monomer.

[0050] The acid component may be any of the above-mentioned specific acid anhydrides having a biphenyl structure, such as 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, and 2,2',3,3'-biphenyltetracarboxylic dianhydride.

[0051] The diamine component may be any of the above-mentioned specific examples of diamines having a biphenyl structure, such as benzidine, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-diethyl-4,4'-diaminobiphenyl, 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3'-diethyl-4,4'-diaminobiphenyl, 3,3'-ditrifluoromethyl-4,4'-diaminobiphenyl, 2,2',3,3'-tetramethyl-4,4'-diaminobiphenyl, and 3,3',4,4'-tetramethyl-4,4'-diaminobiphenyl.

[0052] The component (A) preferably contains a polyamic acid ester structure. The polyamic acid ester structure can suppress the depolymerization reaction of component (A) during thermal curing, resulting in a cured film with high tensile elongation and strength at break. Furthermore, when component (A) is a polyamic acid, metal diffusion occurs due to the interaction between the carboxylic acid and the metal wiring, but the esterification reduces the content of metal components, resulting in a high-resolution pattern without residues in ablation processing using a UV laser. The polyamic acid ester structure is represented by the formula (5) above, 7 is an organic group having 1 to 20 carbon atoms. R 7 More preferably, R is a methyl group. 7 The esterification rate of the carboxylic acid residue including is preferably 10% or more and less than 90%. The carboxylic acid residue includes an imidized portion. When the imidization rate is 10%, the esterification rate is less than 90%. From the perspective of the balance between the metal adhesion and the ablation processing residue and the shape, the esterification rate of the carboxylic acid residue is preferably 10% or more, and more preferably 40% or more.

[0053] For the esterification, it is preferable to use 130 mol % to 200 mol % of the compound represented by formula (6) or formula (7) relative to 100 mol % of all carboxylic acid residues in the structural units derived from the (A) component structure, which is preferable because this can promote both esterification and imidization.

[0054] [ka]

[0055] In formula (6), R 13 R represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and from the viewpoint of reactivity, a hydrogen atom is preferable. 14 represents a hydrogen atom or a monovalent organic group having 1 to 20 carbon atoms, and among these, a nitrogen-containing organic group is preferable. Specifically, a dimethylamino group is preferred in terms of reactivity. 15 each independently represents a monovalent organic group having 1 to 20 carbon atoms.

[0056] [ka]

[0057] In formula (7), R 16 represents a divalent cyclic organic group having 1 to 20 carbon atoms, and among these, a nitrogen-containing cyclic organic group is preferable. 17 Each independently represents a monovalent organic group having 1 to 20 carbon atoms. 15 and R in Eq. (7) 17 becomes a functional group of the ester group of component (A), and the substituent to be introduced can be selected.

[0058] In addition, in order to improve the storage stability of the resin composition of the present invention and to exhibit various functions, the main chain end of the component (A) may be blocked with a terminal blocking agent. Examples of the terminal blocking agent include known ones such as monoamines, acid anhydrides, monocarboxylic acids, monoacid chloride compounds, monoalcohols, and monoactive ester compounds. From the viewpoint of solubility in a developer and mechanical properties of the resulting cured film, the introduction ratio of the terminal blocking agent is preferably 0.1 mol% or more and 60 mol% or less, and particularly preferably 5 mol% or more and 50 mol% or less. A plurality of terminal blocking agents may be reacted to introduce a plurality of different terminal groups.

[0059] As the monoamine used in the terminal blocking agent, known compounds can be used, including M-600, M-2070 (trade names, manufactured by HUNTSMAN Co., Ltd.), aniline, 2-ethynylaniline, 3-ethynylaniline, 4-ethynylaniline, 2-aminobenzoic acid, 3-aminobenzoic acid, 4-aminobenzoic acid, 4-aminosalicylic acid, 2-aminophenol, 3-aminophenol, 4-aminophenol, etc. Two or more of these may be used.

[0060] As the acid anhydride, monocarboxylic acid, monoacid chloride compound, and monoactive ester compound, known compounds can be used, but acid anhydrides such as phthalic anhydride, maleic anhydride, nadic anhydride, cyclohexanedicarboxylic anhydride, and itaconic anhydride, monocarboxylic acids such as 3-carboxyphenol, 4-carboxyphenol, 1-hydroxy-7-carboxynaphthalene, and 1-hydroxy-6-carboxynaphthalene, and active ester compounds in which the carboxyl groups of these are esterified can also be used. Two or more of these may be used.

[0061] The monoalcohol used in the terminal blocking agent may be an aliphatic alcohol such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, or 1-pentanol, or an alkylene oxide-derived monoalcohol such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, or tripropylene glycol monomethyl ether. Two or more of these may be used.

[0062] Furthermore, the various residues introduced into the component (A) used in the present invention can be easily detected by known analytical methods such as NMR.

[0063] The weight average molecular weight of the (A) component is preferably 5,000 or more and 100,000 or less. By making the weight average molecular weight 5,000 or more as calculated in terms of polystyrene by GPC (gel permeation chromatography), mechanical properties such as elongation after curing, strength at break, and elastic modulus can be improved. In order to obtain better mechanical properties, a weight average molecular weight of 20,000 or more is more preferable. In addition, when the (A) component contains two or more types of resins, it is sufficient that the weight average molecular weight of at least one of them is within the above range.

[0064] The component (A) can be obtained by, for example, the following known polymerization method. First, the diamine, the acid dianhydride, and other copolymerization components are dissolved in an organic solvent at room temperature, or at an elevated temperature if necessary, and then heated to polymerize. From the viewpoint of the stability of the solution during the reaction, it is preferable to dissolve the diamine compound with high solubility first. If necessary, other copolymerization components are added, and an acid, an acid anhydride, or a monoamine that serves as an end-capping agent is added and polymerized. When the obtained component (A) is esterified, the carboxylic acid is reacted with an esterifying agent after the above polymerization. In particular, when the formula (6) or formula (7) is used, the imidization rate can be adjusted. The imidization rate may be adjusted by adding an imidization promoter such as pyridine and stirring at 40 to 150°C.

[0065] After polymerization by the above method, other additives may be mixed to form a resin composition, but it is preferable to add it to a large amount of water or a mixture of methanol and water, precipitate it, filter, dry, and isolate it. The drying temperature is preferably 40 to 100°C, more preferably 50 to 80°C. This operation removes unreacted monomers and oligomer components such as dimers and trimers, and can improve the film properties after thermal curing.

[0066] In the present invention, the imidization rate can be easily determined, for example, by the following method. First, the infrared absorption spectrum of the polymer is measured, and the absorption peak (1780 cm) of the imide structure due to the polyimide is detected. -1 Near, 1377cm -1 Next, the polymer was heat-treated at 350°C for 1 hour to obtain a sample with a 100% imidization rate, and the infrared absorption spectrum was measured to confirm the presence of the 1377cm -1 By comparing the peak intensities in the vicinity, the content of imide groups in the resin before heat treatment is calculated, and the imidization rate is determined.

[0067] Examples of organic solvents used in the polymerization of component (A) include, but are not limited to, amides such as N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N,N'-dimethylpropyleneurea, N,N-dimethylisobutyric acid amide, and methoxy-N,N-dimethylpropionamide, cyclic esters such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, γ-caprolactone, ε-caprolactone, and α-methyl-γ-butyrolactone, carbonates such as ethylene carbonate and propylene carbonate, glycols such as triethylene glycol, phenols such as m-cresol and p-cresol, acetophenone, 1,3-dimethyl-2-imidazolidinone, sulfolane, dimethyl sulfoxide, tetrahydrofuran, dimethyl sulfoxide, propylene glycol monomethyl ether acetate, and ethyl lactate.

[0068] The resin composition of the present invention contains a solvent (B). Examples of the solvent include polar aprotic solvents such as N-methyl-2-pyrrolidone, γ-butyrolactone, γ-valerolactone, δ-valerolactone, N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, 1,3-dimethyl-2-imidazolidinone, N,N'-dimethylpropyleneurea, N,N-dimethylisobutyric acid amide, and methoxy-N,N-dimethylpropionamide, ethers such as tetrahydrofuran, dioxane, propylene glycol monomethyl ether, and propylene glycol monoethyl ether, ketones such as acetone, methyl ethyl ketone, and diisobutyl ketone, esters such as ethyl acetate, butyl acetate, isobutyl acetate, propyl acetate, propylene glycol monomethyl ether acetate, and 3-methyl-3-methoxybutyl acetate, alcohols such as ethyl lactate, methyl lactate, diacetone alcohol, and 3-methyl-3-methoxybutanol, and aromatic hydrocarbons such as toluene and xylene. Two or more of these may be contained. Among these, amide-based solvents that have good solubility in the component (A) are preferred, and N-methyl-2-pyrrolidone, N,N'-dimethylpropyleneurea, N,N-dimethylisobutyric acid amide, and methoxy-N,N-dimethylpropionamide are preferred.

[0069] The content of the solvent is preferably 100 parts by mass or more per 100 parts by mass of component (A) in order to dissolve component (A), and is preferably 1,500 parts by mass or less in order to form a coating film with a thickness of 1 μm or more.

[0070] The resin composition of the present invention may contain additives such as adhesion improvers, antioxidants, and surfactants, as long as the effects of the invention are not impaired.

[0071] As the adhesion improver, for metal substrate, nitrogen atom-containing heterocyclic compound can be used, and for silicon substrate, silane coupling agent can be used.Nitrogen atom-containing heterocyclic compound can be used imidazole, pyrazole, indazole, carbazole, pyrazoline, pyrazolidine, triazole, tetrazole, pyridine, piperidine, pyrimidine, pyrazine, triazine, cyanuric acid, isocyanuric acid and their derivatives, more specifically, 1H-benzotriazole, 4-methyl-1H-methylbenzotriazole, 5-methyl-1H-methylbenzotriazole, 4-carboxy-1H-benzotriazole, 5-carboxy-1H-benzotriazole, 1H-tetrazole, 5-methyl-1H-tetrazole, 5-phenyl-1H-tetrazole, etc.

[0072] The content of the nitrogen-containing heterocyclic compound is preferably 0.01 to 5.0 parts by mass, more preferably 0.05 to 3.0 parts by mass, per 100 parts by mass of component (A). When the content of the nitrogen-containing heterocyclic compound is within this range, the developability and the stabilization effect of the base metal can be appropriately maintained.

[0073] Examples of the silane coupling agent include trimethoxyaminopropylsilane, trimethoxycyclohexylepoxyethylsilane, trimethoxyvinylsilane, trimethoxythiolpropylsilane, trimethoxyglycidyloxypropylsilane, tris(trimethoxysilylpropyl)isocyanurate, and a reaction product of trimethoxyaminopropylsilane and an acid anhydride. The reaction product can be used in the form of an amic acid or an imidized state. Examples of the acid anhydride to be reacted include succinic anhydride, maleic anhydride, nadic anhydride, cyclohexanedicarboxylic anhydride, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, and 4,4'-oxydiphthalic dianhydride. The preferred content of the silane coupling agent is 0.01 to 10 parts by mass relative to 100 parts by mass of the (A) component.

[0074] The inclusion of the antioxidant can suppress yellowing of the cured film in the post-curing step and deterioration of mechanical properties such as elongation. In addition, the antioxidant has a rust-preventing effect on metal materials, which can suppress oxidation of the metal materials, which is preferable.

[0075] The antioxidant is preferably a hindered phenol-based antioxidant or a hindered amine-based antioxidant. Examples of the hindered phenol-based antioxidant include, but are not limited to, Irganox245, Irganox3114, and Irganox1010 (all trade names, manufactured by BASF Ltd.), or 2,6-di(t-butyl)-p-cresol. Examples of the hindered amine-based antioxidant include, but are not limited to, TINUVIN144, TINUVIN292 (all trade names, manufactured by BASF Ltd.), 1,2,2,6,6-pentamethyl-4-piperidyl methacrylate, and 2,2,6,6-tetramethyl-4-piperidyl methacrylate. Other antioxidants include phenol, catechol, resorcinol, hydroquinone, 4-t-butylcatechol, 2,6-di(t-butyl)-p-cresol, phenothiazine, and 4-methoxyphenol. The content of the antioxidant is preferably 0.1 to 10.0 parts by mass, more preferably 0.3 to 5.0 parts by mass, per 100 parts by mass of component (A). When the content of the antioxidant is within this range, the developability and the effect of suppressing discoloration due to curing can be appropriately maintained.

[0076] The surfactant makes the surface thickness of the cured film uniform, so that the refractive index of the surface becomes uniform, and a high-resolution pattern can be obtained during ablation processing by laser. Specifically, examples of the surfactant include fluorine-based surfactants such as "Florard" (registered trademark) manufactured by Sumitomo 3M Co., Ltd., "Megafac" (registered trademark) manufactured by DIC Co., Ltd., and "Sulfron" (registered trademark) manufactured by Asahi Glass Co., Ltd., KP341 manufactured by Shin-Etsu Chemical Co., Ltd., DBE manufactured by Chisso Corporation, "Polyflow" (registered trademark) and "Granol" (registered trademark) manufactured by Kyoeisha Chemical Co., Ltd., and BYK manufactured by BYK-Chemie Co., Ltd., and acrylic polymer surfactants such as Polyflow manufactured by Kyoeisha Chemical Co., Ltd. Among these, acrylic polymer surfactants are preferred because they are easily unevenly distributed on the film surface of the cured film due to their low compatibility with the (A) component. The surfactant is preferably contained in an amount of 0.01 to 10 parts by mass relative to 100 parts by mass of the (A) component.

[0077] The resin composition of the present invention may contain other resins as long as the properties of the component (A) are not impaired, but non-fluorine-based resins are preferred. Fluorine-based resins refer to polytetrafluoroethylene, trichlorofluoroethylene, tetrafluoroethylene-hexafluoropropylene, polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene-perfluoroalkyl vinyl ether, tetrafluoroethylene-ethylene, and chlorotrifluoroethylene-ethylene resins. Since fluorine does not absorb in the ultraviolet region, even if it contains a resin or additive that absorbs in the ultraviolet region, it cannot be removed during ablation processing to form a fine pattern, leaving residue, and the interaction with molecular chains and metals is suppressed, resulting in a decrease in physical properties and a decrease in adhesion, so non-fluorine-based resins are preferred.

[0078] Specific examples of the other resins include polyimide resins, polybenzoxazoles, polybenzoxazole precursors, polyamide resins, siloxane resins, maleimide resins, acrylic polymers copolymerized with acrylic acid, epoxy resins, novolac resins, resol resins, polyhydroxystyrene resins, and modified products thereof having crosslinking groups such as methylol groups, alkoxymethyl groups, and epoxy groups introduced therein, and copolymers thereof.

[0079] The viscosity of the resin composition of the present invention is preferably 2 to 5,000 mPa·s. The viscosity can be measured using an E-type rotational viscometer. By adjusting the solid content concentration so that the viscosity is 2 mPa·s or more, it is easy to obtain a desired film thickness. On the other hand, if the viscosity is 5,000 mPa·s or less, it is easy to obtain a highly uniform coating film. A resin composition having such a viscosity can be easily obtained, for example, by adjusting the solid content concentration to 5 to 60 mass%.

[0080] Next, the cured film obtained by curing the resin composition of the present invention will be described. The cured film of the present invention is obtained by curing the resin composition of the present invention. The curing temperature is preferably 150°C or more and 350°C or less. In order to prevent influence on the substrate and semiconductor device and to obtain appropriate elongation and strength, it is more preferable to be 200°C or more and 250°C or less. The curing device may be an oven, a hot plate, infrared irradiation, microwave irradiation, etc., and it is preferable to perform the curing for 20 minutes to several hours. In addition, it can be directly put into a hot plate or oven or other equipment set at the curing temperature, but it can also be put into a curing equipment at around room temperature and heated stepwise. There is no particular limit to the temperature rise rate, but 0.5°C / min to 10°C / min is preferable. The atmosphere during curing may be under air or inert gas such as nitrogen, but it is preferable to be under inert gas, and in the case of air, the curing temperature is preferably 250°C or less.

[0081] The imidization rate of the cured film of the present invention is preferably 97% or more and 100% or less, from the viewpoints of chemical resistance and ablation processability with a UV laser, which will be described later. Moreover, a cured film cured at a curing temperature of 200° C. to 250° C., which causes less damage to the substrate, is preferred. The cured film of the present invention is preferably a cured film patterned by UV laser ablation. The cured film of the present invention has excellent ablation processability by UV laser. The reason is unclear, but it is presumed that the film is made of polyimide obtained from aromatic acid anhydride, so it has excellent UV absorption, has low water absorption, so it is unlikely to foam due to sudden heat generation, and has high breaking strength, so it is resistant to stress changes due to temperature shock around the laser irradiated area.

[0082] The electronic component of the present invention comprises the above-mentioned cured film. Specifically, the electronic component may be provided with a cured film as an insulating film or a protective film.

[0083] Here, examples of electronic components include active components having semiconductors such as transistors, diodes, integrated circuits (ICs), and memories, and passive components such as resistors, capacitors, and inductors. In addition, sealed packages for the purpose of improving the durability of these components and modules in which multiple components are integrated are also included in the electronic components. Electronic components using semiconductors are also called semiconductor devices or semiconductor packages. Other examples include display panels and touch sensor panels.

[0084] Specific examples of the cured film in electronic components include a passivation film for semiconductors, a surface protection film for semiconductor elements and TFTs (Thin Film Transistors), an interlayer insulating film such as an interlayer insulating film between rewirings in multilayer wiring for high-density packaging of 2 to 10 layers, an insulating film for touch panel displays, a protective film, and an insulating layer for organic electroluminescent devices, but are not limited thereto and can have various structures. Among these, it is preferable to use it as an interlayer insulating film in multilayer wiring for high-density packaging. This is because it has lower water absorption than conventional polyimides, so the parasitic components that become a problem when densified do not change, it can be cured at low temperatures, and it can be used as a substrate material for both organic and inorganic substrates, and it has high elongation and strength, so it has high crack resistance against stress caused by multilayering.

[0085] Next, the method for forming a pattern of the cured film of the present invention will be described. The method for producing a pattern of a cured film includes the steps of applying the resin composition of the present invention to a substrate, volatilizing the solvent (B) at 80°C or higher and lower than 150°C, curing at 150°C or higher and 250°C or lower, and ablation processing using a UV laser.

[0086] First, the step of applying the resin composition of the present invention to a substrate will be described. Examples of substrates include, but are not limited to, silicon wafers, ceramics, gallium arsenide, organic circuit boards, inorganic circuit boards, composite substrates of silicon wafers and sealing resins such as epoxy resins, and substrates on which circuit constituent materials are disposed.

[0087] Examples of organic circuit boards include glass substrate copper-clad laminates such as glass cloth-epoxy copper-clad laminates, composite copper-clad laminates such as glass nonwoven cloth-epoxy copper-clad laminates, temporary carrier substrates, heat-resistant thermoplastic substrates such as polyetherimide resin substrates, polyetherketone resin substrates, and polysulfone resin substrates, and flexible substrates such as polyester copper-clad film substrates and polyimide copper-clad film substrates. Examples of inorganic circuit boards include glass substrates, ceramic substrates such as alumina substrates, aluminum nitride substrates, and silicon carbide substrates, and metal substrates such as aluminum-based substrates and iron-based substrates. Examples of circuit components include conductors containing metals such as silver, gold, and copper, resistors containing inorganic oxides, low dielectrics containing glass-based materials and / or resins, high dielectrics containing resins and high-dielectric-constant inorganic particles, and insulators containing glass-based materials.

[0088] Regarding metal wiring on a circuit board or the like, the surface condition changes when oxidized in air, so it is preferable to perform an oxidation treatment in advance using oxygen plasma treatment or hydrogen peroxide water.

[0089] Examples of the coating method include spin coating using a spinner, spray coating, roll coating, screen printing, blade coater, die coater, calendar coater, meniscus coater, bar coater, roll coater, comma roll coater, gravure coater, screen coater, slit die coater, etc. The coating thickness varies depending on the coating method, the solids concentration of the composition, the viscosity, etc., but the coating is usually performed so that the film thickness after drying is 0.1 to 150 μm.

[0090] In order to enhance the adhesion between a substrate such as a silicon wafer and a resin composition, the substrate may be pretreated with the above-mentioned silane coupling agent. For example, a solution in which a silane coupling agent is dissolved in a solvent such as isopropanol, ethanol, methanol, water, tetrahydrofuran, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, ethyl lactate, or diethyl adipate at a concentration of 0.5 to 20% by mass is used for surface treatment by spin coating, immersion, spray coating, steam treatment, or the like. In some cases, a heat treatment up to 50°C to 300°C is then performed to promote the reaction between the substrate and the silane coupling agent.

[0091] Next, the step of volatilizing the solvent (B) at a temperature of 80° C. or higher and lower than 150° C. will be described. The drying step for volatilizing the solvent is preferably carried out using an oven, a hot plate, infrared irradiation, microwave irradiation, etc., at a temperature in the range of 50° C. to 150° C. for 1 minute to several hours. The drying atmosphere may be air or an inert gas such as nitrogen.

[0092] Next, the step of curing at 150° C. or higher and 250° C. or lower will be described. The curing conditions are preferably 150°C or higher and 350°C or lower. In order to prevent the influence on the substrate and semiconductor device and to obtain appropriate elongation and strength, 200°C or higher and 250°C or lower are more preferable. The same equipment as that used for drying can be used for curing, and curing is preferably performed for 20 minutes to several hours. The material can be directly placed in equipment such as a hot plate or oven set to the curing temperature, but it can also be placed in the curing equipment at around room temperature and heated stepwise. There is no particular limit to the temperature rise rate, but 0.5°C / min to 10°C / min is preferable. The atmosphere during curing may be air or inert gas such as nitrogen, but inert gas is preferable. In addition, when in air, the curing temperature is preferably 250°C or lower.

[0093] Next, we will explain the process of ablation using a UV laser. The cured film is irradiated with a UV laser to perform an ablation process and form a pattern in the desired location.

[0094] The irradiation conditions of this UV laser are not particularly limited, but usually excimer lasers such as ArF (193 nm), KrF (248 nm), XeCl (308 nm), XeCl (351 nm), and YAG laser (355 nm) light are used. Among these, excimer lasers are preferred because they are less susceptible to heat during processing and can form high-resolution patterns with via diameters of 5 μm or less, and processing with KrF (248 nm) is even more preferred because an appropriate absorbance of the cured film can be obtained at the wavelength of the UV laser, resulting in a high-resolution pattern without residue.

[0095] When forming a pattern, 5 to 10,000 mJ / cm 2 The UV laser light having an energy density of 100 nm to 3000 Hz is irradiated onto the cured film-formed substrate for a predetermined time via an optical system having a reduction ratio of 0.1 to 20 times at a repetitive pulse frequency of 1 to 3000 Hz, either directly or using a patterning mask having a desired shape, to form a pattern.

[0096] The cured film of the resin composition of the present invention can be formed by irradiating a UV laser with an irradiation energy of 500 to 1000 mJ / cm 2 By setting the value at 100 to 500 mJ / cm, a rectangular tapered shape can be obtained. 2 By controlling the energy density to less than 100 nm, the taper shape can be controlled. This is preferable because it is easy to control the shape in an interlayer insulating film in which different shapes are required for each layer due to differences in wiring thickness and pattern formation density.

[0097] In the present invention, the absorbance of the cured film obtained by curing the resin composition is preferably 0.05 to 0.9 per 1 μm of film thickness at the wavelength of the UV laser, and more preferably 0.07 to 0.3. This range is preferable because the UV laser can form a pattern and is unlikely to cause abnormal shapes.

[0098] The cured film of the present invention can also be ablated with a carbon dioxide laser. Although the carbon dioxide laser has a lower resolution than the UV laser, the equipment cost is low and the carbon dioxide laser is economical, so that the carbon dioxide laser may be used in applications that do not require high resolution.

[0099] Next, an application example of the resin composition of the present invention to a semiconductor device having bumps will be described with reference to the drawings (Application Example 1). FIG. 1 is an enlarged cross-sectional view of a pad portion of a semiconductor device having bumps of the present invention. As shown in FIG. 1, a passivation film 3 is formed on an aluminum (hereinafter, Al) pad 2 for input / output on a silicon wafer 1, and a via hole is formed in the passivation film 3. Furthermore, an insulating film 4 is formed on the insulating film 3 as a pattern using the resin composition of the present invention, and a metal (Cr, Ti, etc.) film 5 is formed so as to be connected to the Al pad 2, and a metal wiring (Al, Cu, etc.) 6 is formed by electrolytic plating or the like. The metal film (Cr, Ti, etc.) 5 is etched around the solder bump 10 to insulate each pad. Furthermore, an insulating film 7 is formed on the insulating film 3 as a pattern using the resin composition of the present invention. A barrier metal 8 and a solder bump 10 are formed on the insulated pad. Since the resin of the present invention has excellent elongation, the resin itself deforms to relieve stress from the sealing resin even during mounting, preventing damage to the bumps, wiring, and low-k layer, and providing a highly reliable semiconductor device.

[0100] Next, a detailed method for fabricating a semiconductor device is described in FIG. 2. As shown in FIG. 2, 2a, an Al pad 2 for input / output and a passivation film 3 are formed on a silicon wafer 1, and an insulating film 4 is formed as a pattern using the resin composition of the present invention. Then, as shown in FIG. 2, 2b, a metal (Cr, Ti, etc.) film 5 is formed so as to be connected to the Al pad 2, and as shown in FIG. 2, 2c, a metal wiring (Al, Cu, etc.) 6 is formed by plating. Next, as shown in FIG. 2, 2d', the resin composition of the present invention is applied and cured, and then an ablation process is performed to form an insulating film 7 as a pattern as shown in FIG. 2, 2d. Further wiring (so-called rewiring) can be formed on the insulating film 7. When forming a multilayer wiring structure of two or more layers, the above steps are repeated to form a multilayer wiring structure in which two or more rewiring layers are separated by an interlayer insulating film obtained from the resin composition of the present invention. There is no upper limit to the number of layers in the multilayer wiring structure, but a structure of 10 layers or less is often used. At this time, the resin composition of the insulating film 7 is processed to be thick at the scribe line 9. When forming a multi-layer wiring structure having three or more layers, the above steps can be repeated to form each layer.

[0101] 2, barrier metal 8 and solder bumps 10 are formed, and then dicing is performed along the final scribe lines 9 to separate the wafer into individual chips.

[0102] Next, an application example 2 to a semiconductor device having bumps using the resin composition of the present invention will be described with reference to the drawings. FIG. 3 is an enlarged cross-sectional view of a pad portion of a semiconductor device having an insulating film of the present invention, and has a structure called a fan-out wafer level package (fan-out WLP). As in the above application example 1, a silicon wafer 1 on which an Al pad 2 and a passivation film 3 are formed is diced and cut into chips, and then sealed with a resin 11. An insulating film 4 is formed as a pattern by the resin composition of the present invention over the sealing resin 11 and the chip, and further a metal (Cr, Ti, etc.) film 5 and metal wiring 6 are formed. Then, a barrier metal 8 and a solder bump 10 are formed in an opening of an insulating film 7 formed on the sealing resin outside the chip. The fan-out WLP is a semiconductor package in which an extension part is provided around a semiconductor chip using a sealing resin such as an epoxy resin, rewiring is performed from an electrode on the semiconductor chip to the extension part, and solder balls are also mounted on the extension part to ensure the required number of terminals.

[0103] In addition, there exists a type of fan-out WLP package that is produced by a process called RDL-first, in which a temporary bonding material is placed on a support substrate as an interlayer insulating film between rewirings, a silicon chip and a sealing resin are placed on top of the interlayer insulating film, and then the support substrate on which the temporary bonding material is placed is peeled off from the rewirings. The resin composition of the present invention can be used in the same manner in the RDL-first process.

[0104] Next, a third application example of the inductor device coil component using the resin composition of the present invention will be described with reference to the drawings. FIG. 4 is a cross-sectional view of a coil component having an insulating film of the present invention. As shown in FIG. 4, an insulating film 13 is formed on a substrate 12, and an insulating film 14 is formed thereon as a pattern. Ferrite or the like is used as the substrate 12. The resin composition of the present invention may be used for either the insulating film 13 or the insulating film 14. A metal (Cr, Ti, etc.) film 15 is formed in the opening of this pattern, and a metal wiring (Ag, Cu, etc.) 16 is plated on the metal wiring 15. The metal wiring 16 (Ag, Cu, etc.) is formed in a spiral shape. The steps 13 to 16 are repeated multiple times and stacked to provide a function as a coil. Finally, the metal wiring 16 (Ag, Cu, etc.) is connected to an electrode 18 by a metal wiring 17 (Ag, Cu, etc.) and sealed with a sealing resin 19.

[0105] The antenna element of the present invention is an antenna element comprising at least one or more antenna wirings and the cured film of the present invention, the antenna wirings including at least one type of antenna selected from the group consisting of meandering loop antennas, coiled loop antennas, meandering monopole antennas, meandering dipole antennas, and microstrip antennas, and the area occupied by each antenna portion of the antenna wiring is 1000 mm2 or less. 2 The cured film is preferably an insulating film that provides insulation between the ground and the antenna wiring.

[0106] Here, the antenna element refers to an electronic component that utilizes passive components such as resistors, inductors, and capacitors and has the function of transmitting and receiving radio waves. The material used for the antenna wiring is not particularly limited as long as it has conductivity, and examples thereof include metal materials such as copper, gold, silver, platinum, aluminum, molybdenum, and titanium. These may be laminates or alloys of different metals, or may be composites with organic substances such as polymers. In addition, carbon materials such as graphite, graphene, and carbon nanotubes, and conductive polymers may be used. Among these, copper is preferred because of its excellent cost, conductivity, and stability.

[0107] The antenna element of the present invention will be specifically described with reference to FIG. 5. FIG. 5 is a schematic diagram of a coplanar-feed type microstrip antenna, which is a type of planar antenna. 5a shows a cross-sectional view, and 5b shows a top view. First, the formation method will be described. The thermosetting resin composition of the present invention is applied onto copper foil and pre-baked. Next, copper foil is laminated and thermally cured to form a cured film having copper foil on both sides. After that, patterning is performed by a subtractive method, and an antenna element having an antenna pattern of copper wiring of a microstrip line (MSL) shown in FIG. 5 is obtained.

[0108] Next, the antenna pattern in Fig. 5 will be described. In 5a, 55 denotes the ground (all over), and 56 denotes an insulating film that becomes the substrate of the antenna. The upper layers 51 to 53 denote the cross section of the antenna wiring obtained by the above-mentioned patterning. The ground wiring thickness J and the antenna wiring thickness K can be any thickness depending on the impedance design, but are generally 2 to 20 µm. In 5b, 51 denotes the antenna part, 52 denotes a matching circuit, 53 denotes an MSL feed line, and 54 denotes a feed point. To match the impedance of the antenna part 51 and the MSL feed line 53, the length M of the matching circuit 52 is 1 / 4 λr (λr = (wavelength of transmitted radio wave) / (dielectric constant of insulating material) 1 / 2 ). The width W and length L of the antenna portion 51 are designed to be 1 / 2λr. The antenna portion length L may be set to 1 / 2λr or less depending on the impedance design.

[0109] The cured film of the present invention has low water absorption, and therefore can provide an antenna element with small fluctuations in characteristics due to the environment. In addition, due to these characteristics, the antenna element using the insulating film of the present invention is particularly suitable as a high-frequency antenna, and the area of ​​the antenna part (=L×W) is 1000 mm 2 By making the dimensions as follows, a small antenna element can be formed. In this way, an antenna element for high frequencies is obtained.

[0110] The semiconductor package of the present invention is a semiconductor package including at least a semiconductor element, a rewiring layer, a sealing resin, and an antenna wiring, the antenna wiring including at least one antenna selected from the group consisting of a meandering loop antenna, a coiled loop antenna, a meandering monopole antenna, a meandering dipole antenna, and a microstrip antenna, and the area occupied by each antenna portion of the antenna wiring is 1000 mm2 or less. 2 It is preferable that the insulating layer of the redistribution layer and / or the sealing resin includes the cured film of the present invention, and that the sealing resin is located between the ground and the antenna wiring.

[0111] Materials used for the antenna wiring include those described in the description of the antenna element above. In addition, examples of the semiconductor element include an integrated circuit (RFIC) that processes signals transmitted and received by the antenna, and may have semiconductor elements such as an amplifier and a noise filter. The rewiring layer is preferably made of 1 to 3 layers of metal wiring and 1 to 4 layers of insulating layers from the viewpoints of cost and reliability, but is not limited thereto. The insulating layer is preferably the cured film of the present invention. The sealing resin is preferably the cured film of the present invention, but when used in the insulating layer of the rewiring layer, there is no restriction and any sealing agent can be used, and a mixture of epoxy resin and inorganic filler is generally used.

[0112] A semiconductor package including an IC chip (semiconductor element), a rewiring layer, a sealing resin, and an antenna wiring will be described. FIG. 6 is a schematic diagram of a cross section of a semiconductor package including an IC chip (semiconductor element), a rewiring, a sealing resin, and an antenna element. On an electrode pad 602 of an IC chip 601, a rewiring layer (two copper layers, three insulating layers) is formed by copper wiring 609 and an insulating film 610 formed by the cured film of the present invention. The thickness of the copper wiring is preferably 2 to 10 μm in order to reduce noise. The thickness of the insulating layer can be set according to the thickness of the copper wiring, and it is preferable to make it 2 to 5 μm thicker than the copper wiring from the viewpoint of insulation. A barrier metal 611 and a solder bump 612 are formed on the pad of the rewiring layer (copper wiring 609 and insulating film 610). In order to seal the IC chip, a first sealing resin 608 made of the cured film of the present invention is formed, and a copper wiring 609 serving as a ground for an antenna is further formed thereon. A first via wiring 607 is formed to connect the ground 606 and the rewiring layer (copper wiring 609 and insulating film 610) through a via hole formed in the first sealing resin 608. A second sealing resin 605 made of the cured film of the present invention is formed on the first sealing resin 608 and the ground 606, and a planar antenna wiring 604 is formed thereon. A second via wiring 603 is formed to connect the planar antenna wiring 604 and the rewiring layer (copper wiring 609 and insulating film 610) through a via hole formed in the first sealing resin 608 and the second sealing resin 605. The thickness of each insulating film 610 is preferably 10 to 20 μm, and the thicknesses of the first sealing resin and the second sealing resin are preferably 50 to 200 μm and 100 to 400 μm, respectively. Since the cured film of the present invention has low water absorption, the semiconductor package having the obtained antenna element has small characteristic variations due to the environment and is excellent in reliability. EXAMPLES

[0113] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. First, the evaluation method in each example and comparative example will be described. For the evaluation, the resin composition (hereinafter referred to as varnish) of each example was used, which had been filtered in advance through a polytetrafluoroethylene (PTFE) filter (manufactured by Sumitomo Electric Industries, Ltd.) with an average pore size of 1 μm.

[0114] (1) Molecular weight measurement, esterification rate measurement The weight average molecular weight (Mw) of component (A) was confirmed using a GPC (gel permeation chromatography) device Waters 2690-996 (manufactured by Japan Waters Co., Ltd.) Measurements were performed using N-methyl-2-pyrrolidone (hereinafter referred to as NMP) as the developing solvent, and the weight average molecular weight (Mw) and dispersity (PDI=Mw / Mn) were calculated in terms of polystyrene.

[0115] In addition, the esterification rate of component (A) is 400 MHz, 1 Using a H-NMR (nuclear magnetic resonance) device (AL-400 manufactured by JEOL Ltd.), measurements were taken in a deuterated dimethyl sulfoxide solution with 16 cumulative measurements, and the esterification rate was calculated based on the integral value of the protons of the esterified substituents.

[0116] (2) Measurement of imidization rate of cured film The varnish was spin-coated onto a 4-inch silicon wafer and dried at 120°C for 3 minutes. When a varnish containing a photobase generator was used, 300 mJ / cm was applied to the entire surface using PLA. 2 The curing conditions were as shown in Table 2. The infrared absorption spectrum was measured and the absorption peak of the imide structure (1780 cm) was observed. -1 Near, 1377cm -1 The presence of a nearby Next, the coating film was cured at 350 °C for 1 hour, and the infrared absorption spectrum was measured as a sample with a 100% imidization rate.-1 By comparing the peak intensities around the peak, the content of imide groups in the resin before heat treatment was calculated, and the imidization rate was determined. The infrared absorption spectrum was measured using an "FT-720" (trade name, manufactured by Horiba, Ltd.) measuring device.

[0117] (3) Measurement of elongation at break and strength at break of cured film The varnish was applied to a 6-inch silicon wafer by spin coating using the ACT-8 coating and developing device, and prebaked at 120°C for 3 minutes to give a film thickness of 11 μm. When a varnish containing a photobase generator was used, PLA was used to coat the entire surface at 300 mJ / cm. 2 The sample was exposed to light, and heated to the curing temperature shown in Table 2 at a rate of 3.5°C / min using an inert oven CLH-21CD-S (manufactured by Koyo Thermo Systems Co., Ltd.) at an oxygen concentration of 20 ppm or less, and cured for 1 hour at the curing temperature shown in Table 2. When the temperature reached 50°C or less, the silicon wafer was removed and immersed in 45% by mass hydrofluoric acid for 5 minutes to peel off the cured film of the resin composition from the wafer. This film was cut into strips 1.5 cm wide and 9 cm long, and measured for elongation at break (%) and strength at break (MPa) using a Tensilon RTM-100 (manufactured by Orientec Co., Ltd.) at room temperature of 23.0°C and humidity of 45.0% RH at a tensile speed of 50 mm / min (chuck spacing = 2 cm). Measurements were performed on 10 strips per specimen, and the average of the top 5 highest values ​​was calculated from the results (significant figures = 2 digits).

[0118] (4) Measurement of water absorption rate A free-standing cured film was prepared in the same manner as described above in "(2) Measurement of elongation at break and strength at break of cured film" and treated for 20 hours under saturated conditions of 23°C, 100% RH, and 1 atm using a high temperature and humidity tester (HAST CHAMBER EHS-211MD, manufactured by Tabai Spec Co., Ltd.), and then the film was held at 120°C for 30 minutes in a thermogravimetric analyzer (TGA). The water absorption rate was calculated from the weight loss rate before and after heating.

[0119] (5) Pattern evaluation The varnish was applied by spin coating using a coating and developing device ACT-8 (Tokyo Electron Ltd.) onto an 8-inch silicon wafer on which a 100 nm copper sputtered film had been formed, and pre-baked at 120°C for 3 minutes. When a varnish containing a photobase generator was used, 300 mJ / cm was applied to the entire surface using PLA. 2 The curing temperature was raised at a rate of 3.5°C / min to the curing temperature shown in Table 2 at an oxygen concentration of 20 ppm or less using an inert oven CLH-21CD-S (manufactured by Koyo Thermo Systems Co., Ltd.), and curing was carried out for 1 hour at the curing temperature shown in Table 2. The resulting cured film having a thickness of 10 μm was exposed to light at 600 mJ / cm using a carbon dioxide laser (wavelength 10,600 nm) or a KrF excimer laser (wavelength 248 nm), which is a UV laser. 2 The via pattern was formed with an irradiation dose of 100 nm. The minimum diameter (μm) of the via pattern that could be opened was defined as the resolution.

[0120] (6) Copper substrate adhesion evaluation The adhesion to metallic copper was evaluated by the following method.

[0121] First, a cured film was formed on a metal copper-plated substrate with a thickness of about 3 μm in the same manner as in "(2) Measurement of the imidization rate of the cured film" above. Using a single-edged blade, 10 rows and 10 columns of 1 mm intervals were cut into the obtained cured film on the copper substrate. The adhesive properties between the metal material and the cured resin film were then evaluated based on how many of the 100 squares peeled off when peeled off with "Scotch Tape" (registered trademark). In the peel test, 0 peeled pieces were scored as 5, 1 to less than 10 peeled pieces were scored as 4, 10 to less than 30 peeled pieces were scored as 3, 30 to less than 50 peeled pieces were scored as 2, and 50 or more peeled pieces were scored as 1.

[0122] The fewer the number of peeled pieces, the better the adhesion.

[0123] (7) Storage stability of varnish The viscosity of the varnish after preparation and after standing at 23° C. for 2 weeks were measured, and the rate of change in viscosity before and after standing was calculated. The smaller the rate of change in viscosity before and after standing, the better the storage stability.

[0124] (Synthesis Example 1) Synthesis of (A-1) Under a dry nitrogen stream, 4,4'-methylenebis(cyclohexylamine) (HM) (21.0 g, 0.1 mol) was dissolved in 250 g of N-methyl-2-pyrrolidone (NMP), and then decamethylene bistrimellitate dianhydride (10BA) (52.3 g, 0.1 mol) was added and reacted at 40°C for 1 hour. The temperature was then raised to 80°C and the mixture was stirred for another 2 hours. After the reaction was completed, the mixture was cooled to room temperature and diluted with NMP to a solid content concentration of 20 wt%, to obtain an NMP solution of a polyimide precursor polymer (A-1) (solid content concentration 20 wt%). The esterification rate of the obtained (A-1) was 0%, the weight average molecular weight was 50,500, and the PDI was 2.4.

[0125] (Synthesis Example 2) Synthesis of (A-2) Except for using trans-cyclohexanediamine (t-CHDA) (11.4 g, 0.1 mol) instead of HM, an NMP solution (solid content concentration 20 wt%) of a polyimide precursor polymer (A-2) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-2) was 0%, the weight average molecular weight was 52,500, and the PDI was 2.5.

[0126] (Synthesis Example 3) Synthesis of (A-3) Except for using 2,2'-trifluoromethyl-4,4'-aminobicyclohexane (H-TFMB) (33.2 g, 0.1 mol) instead of HM, an NMP solution (solid content concentration 20 wt%) of a polyimide precursor polymer (A-3) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-3) was 0%, the weight average molecular weight was 53,000, and the PDI was 2.5.

[0127] (Synthesis Example 4) Synthesis of (A-4) Except for using hexadecamethylene bistrimellitate dianhydride (16BA) (60.7 g, 0.1 mol) instead of 10BA, an NMP solution (solid concentration 20 wt%) of a polyimide precursor polymer (A-4) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-4) was 0%, the weight average molecular weight was 50,000, and the PDI was 2.3.

[0128] (Synthesis Example 5) Synthesis of (A-5) Except for using hexamethylene bistrimellitate dianhydride (6BA) (46.6 g, 0.1 mol) instead of 10BA, an NMP solution (solid content concentration 20 wt%) of a polyimide precursor polymer (A-5) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-5) was 0%, the weight average molecular weight was 49,000, and the PDI was 2.2.

[0129] (Synthesis Example 6) Synthesis of (A-6) Under a dry nitrogen stream, 4,4'-methylenebis(cyclohexylamine) (HM) (21.0 g, 0.1 mol) was dissolved in 250 g of dimethyl sulfoxide (DMSO), and then decamethylenebistrimellitic acid amide dianhydride (10BAm) (52.1 g, 0.1 mol) was added and reacted at 40°C for 1 hour. The temperature was then raised to 80°C and the mixture was stirred for another 2 hours. After the reaction was completed, the mixture was cooled to room temperature and diluted with DMS to a solid content concentration of 20 wt%, to obtain a DMSO solution of a polyimide precursor polymer (A-6) (solid content concentration 20 wt%). The esterification rate of the obtained (A-5) was 0%, the weight average molecular weight was 52,000, and the PDI was 2.4. This polymerization was carried out in DMSO because the viscosity increased due to insufficient solubility when NMP was used as the solvent.

[0130] (Synthesis Example 7) Synthesis of (A-7) A DMSO solution (solid concentration 20 wt%) of a polyimide precursor polymer (A-7) was obtained in the same manner as in Synthesis Example 6, except that decamethylene bistrimellitic acid thioester dianhydride (10BS) (55.5 g, 0.1 mol) was used instead of 10BAm. The esterification rate of the obtained (A-7) was 0%, the weight average molecular weight was 45,000, and the PDI was 2.2.

[0131] (Synthesis Example 8) Synthesis of (A-8) Except for changing the amount of 10BA to (26.1 g, 0.05 mol) and using 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) (14.7 g, 0.05 mol) as the acid component, an NMP solution (solid concentration 20 wt%) of a polyimide precursor polymer (A-8) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-8) was 0%, the weight average molecular weight was 52,000, and the PDI was 2.4.

[0132] (Synthesis Example 9) Synthesis of (A-9) Except for changing the amount of 10BA to 15.7 g (0.03 mol) and using BPDA (20.6 g, 0.07 mol) as the acid component, an NMP solution (solid concentration 20 wt%) of a polyimide precursor polymer (A-9) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-9) was 0%, the weight average molecular weight was 53,000, and the PDI was 2.5.

[0133] (Synthesis Example 10) Synthesis of (A-10) Except for changing the amount of HM to 10.5 g (0.05 mol) and using 2,2'-ditrifluoromethyl-4,4'-diaminobiphenyl (TFMB) (16.0 g, 0.05 mol) as the diamine component, an NMP solution (solid concentration 20 wt%) of a polyimide precursor polymer (A-10) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-10) was 0%, the weight average molecular weight was 54,000, and the PDI was 2.5.

[0134] (Synthesis Example 11) Synthesis of (A-11) Except for changing the amount of HM to 6.3 g (0.03 mol) and using TFMB (22.4 g, 0.07 mol) as the diamine component, an NMP solution (solid concentration 20 wt%) of a polyimide precursor polymer (A-11) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-11) was 0%, the weight average molecular weight was 54,000, and the PDI was 2.5.

[0135] (Synthesis Example 12) Synthesis of (A-12) Under a dry nitrogen stream, HM (21.0 g, 0.1 mol) was dissolved in 250 g of NMP, 10BA (52.3 g, 0.1 mol) was added, and the mixture was reacted at 40°C for 1 hour. The mixture was then heated to 80°C and stirred for another 2 hours. Then, a solution of N,N-dimethylformamide dimethyl acetal (35.8 g, 0.3 mol) diluted with 10 g of NMP was added dropwise over 10 minutes. After the addition, the mixture was stirred at 40°C for 3 hours. After the reaction was completed, the solution was poured into 2 L of water, and the precipitate of the polymer solid was collected by filtration. The polymer solid was dried in a vacuum dryer at 50°C for 72 hours to obtain a polyimide precursor (A-12). The esterification rate of the resin thus obtained by methyl groups was 50%. The weight average molecular weight was 55,300, and the PDI was 2.4.

[0136] (Synthesis Example 13) Synthesis of (A-13) Except for using pyromellitic anhydride (PMDA) (21.2 g, 0.1 mol) instead of 10BA, an NMP solution (solid content concentration 20 wt%) of a polyimide precursor polymer (A-13) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-13) was 0%, the weight average molecular weight was 50,000, and the PDI was 2.3.

[0137] (Synthesis Example 14) Synthesis of (A-14) Except for using 4,4'-diaminodiphenyl ether (ODA) (20.2 g, 0.1 mol) instead of HM, an NMP solution (solid content concentration 20 wt%) of a polyimide precursor polymer (A-14) was obtained in the same manner as in Synthesis Example 1. The esterification rate of the obtained (A-14) was 0%, the weight average molecular weight was 55,000, and the PDI was 2.5. (Synthesis Example 15) Synthesis of (A-15) Under a dry nitrogen stream, 62.04g (0.2 mol) of oxydiphthalic anhydride (ODPA) was dissolved in 1000g of NMP. 96.72g (0.16 mol) of diamine (HA) having the following structure and 4.97g (0.02 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane (SiDA) were added together with 100g of NMP, and the mixture was reacted at 20°C for 1 hour, and then at 50°C for 2 hours. Next, 4.37g (0.04 mol) of 3-aminophenol (MAP) was added together with 30g of NMP as a terminal blocking agent, and the mixture was reacted at 50°C for 2 hours. After that, a solution of 47.66g (0.4 mol) of N,N-dimethylformamide dimethylacetal diluted with 50g of NMP was added dropwise over 10 minutes. After the dropwise addition, the mixture was stirred at 50°C for 3 hours. After the stirring was completed, the solution was cooled to room temperature, and then poured into 1 L of water to obtain a precipitate. The precipitate was collected by filtration, washed three times with water, and then dried in a vacuum dryer at 80°C for 20 hours to obtain a powder of polyimide precursor resin (A-15). The esterification rate of the resin thus obtained by methyl groups was 50%. The molecular weight of the polyimide precursor (A-15) was measured by gel permeation chromatography (standard polystyrene equivalent), and the weight average molecular weight (Mw) was 25,000 and the PDI was 2.3.

[0138] [ka]

[0139] The components of the polyimide precursor obtained in the synthesis examples are shown in Table 1.

[0140] [Table 1]

[0141] Example 1 The NMP solution (solid content concentration 20 wt%) of the polyimide precursor (A-1) synthesized in Synthesis Example 1 was filtered through a syringe filter (made of PTFE) with a pore size of 1.0 μm as described above to obtain a varnish. The obtained varnish was subjected to various measurements using the methods described in (1) to (7) above. The curing temperature was 180° C. Example 2 The same procedure as in Example 1 was carried out except that the curing temperature was set to 200° C. However, since the varnish used was the same as in Example 1, evaluation of storage stability was omitted. Example 3 The same procedure as in Example 1 was carried out except that the curing temperature was set to 230° C. However, since the varnish used was the same as in Example 1, evaluation of storage stability was omitted. Example 4 The same procedure as in Example 1 was carried out except that the curing temperature was set to 250° C. However, since the varnish used was the same as in Example 1, evaluation of storage stability was omitted. Example 5 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-2) synthesized in Synthesis Example 2, and the curing temperature was set to 230°C.

[0142] Example 6 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-3) synthesized in Synthesis Example 3, and the curing temperature was set to 230°C. Example 7 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-4) synthesized in Synthesis Example 4, and the curing temperature was set to 230°C. Example 8 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-5) synthesized in Synthesis Example 5, and the curing temperature was set to 230°C. Example 9 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-6) synthesized in Synthesis Example 6, and the curing temperature was set to 230°C. Example 10 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-7) synthesized in Synthesis Example 7, and the curing temperature was set to 230°C.

[0143] Example 11 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-8) synthesized in Synthesis Example 8, and the curing temperature was set to 230°C. Example 12 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-9) synthesized in Synthesis Example 9, and the curing temperature was set to 230°C. (Example 13) The same procedure as in Example 1 was repeated except that a solution (solid content concentration 20 wt%) in which the polyimide precursor (A-10) synthesized in Synthesis Example 10 was dissolved in NMP was used instead of the polyimide precursor (A-1), and the curing temperature was set to 230°C. Example 14 The same procedure as in Example 1 was repeated except that a solution (solid content concentration 20 wt%) in which the polyimide precursor (A-11) synthesized in Synthesis Example 11 was dissolved in NMP was used instead of the polyimide precursor (A-1), and the curing temperature was set to 230°C. Example 15 The same procedure as in Example 1 was repeated except that a solution (solid content concentration 20 wt%) in which the polyimide precursor (A-12) synthesized in Synthesis Example 12 was dissolved in NMP was used instead of the polyimide precursor (A-1), and the curing temperature was set to 230°C.

[0144] Comparative Example 1 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-13) synthesized in Synthesis Example 13, and the curing temperature was set to 230°C. Comparative Example 2 The same procedure as in Example 1 was repeated, except that the polyimide precursor (A-1) was replaced with an NMP solution (solid content concentration: 20 wt%) of the polyimide precursor (A-14) synthesized in Synthesis Example 14, and the curing temperature was set to 230°C. Comparative Example 3 The same procedure as in Comparative Example 1 was repeated except that 3 parts by weight of cyclohexylamine-2-hydroxycinnamate was added as a photobase generator based on 100 parts by weight of the polyimide precursor (A-13). Comparative Example 4 3.5 g of the polyimide precursor (A-15) synthesized in Synthesis Example 15, 0.5 g of a 5-naphthoquinone diazide compound (product name "TPPA-280" manufactured by Toyo Gosei Co., Ltd.), and 0.07 g of 1H-benzotriazole were diluted with NMP to a solid concentration of 20 wt%, and filtered through a syringe filter (made of PTFE) with a pore size of 1.0 μm to obtain a varnish. The obtained varnish was subjected to various measurements using the methods described in (1) to (7) above. The results of the examples and comparative examples are shown in Table 2.

[0145] [Table 2] [Explanation of symbols]

[0146] 1. Silicon wafer 2 Aluminum pad 3 Passivation film 4. Insulating film 5 Metal (Cr, Ti, etc.) film 6 Metal wiring (Al, Cu, etc.) 7. Insulating Film 8 Barrier Metal 9 Scribe Line 10 Solder Bumps 11 Sealing resin 12 Substrate 13. Insulating film 14 Insulating film 15 Metal (Cr, Ti, etc.) film 16 Metal wiring (Ag, Cu, etc.) 17 Metal wiring (Ag, Cu, etc.) 18 electrodes 19 Sealing resin 51 Antenna section 52 Matching Circuit 53 MSL power supply line 54 Power supply point 55 Grand 56 Insulating Film J Ground wiring thickness K Antenna wiring thickness M Matching circuit length L Antenna length W Antenna width 601 IC chip 602 Electrode Pads 603 Second via wiring 604 Planar antenna wiring 605 Second sealing resin 606 Grand 607 First via wiring 608 First sealing resin 609 Copper wiring 610 Insulating film 611 Barrier Metal 612 Solder Bump

Claims

1. The present invention comprises a polyimide precursor (A) having an acid anhydride residue represented by formula (1) and an alicyclic diamine residue, and a solvent (B), The alicyclic diamine residue is trans-1,4-cyclohexanediamine, trans-1,3-cyclohexanediamine, trans-1,2-cyclohexanediamine, cis-1,4-cyclohexanediamine, cis-1,3-cyclohexanediamine, cis-1,2-cyclohexanediamine, 1,2-bis(aminomethyl)cyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 4,4'-methylenebis(cyclohexylamine), 4,4'-methylenebis(2-methylcyclohexylamine). , 4,4'-isopropylidenebis(cyclohexylamine), 4,4'-isopropylidenebis(2-methylcyclohexylamine), 4,4'-hexafluoroisopropylidenebis(cyclohexylamine), 4,4'-hexafluoroisopropylidenebis(2-methylcyclohexylamine), 4,4'-bicyclohexyldiamine, 2,2'-methyl-4,4'-aminobicyclohexane, and 2,2'-trifluoromethyl-4,4'-aminobicyclohexane. 【Chemistry 1】 (In the formula, X 1 and X 2 represents an oxygen atom, a sulfur atom, or an -NH- group; and n represents an integer of 4 to 20.

2. X represented by the formula (1) 1 and X 2 The resin composition according to claim 1 , wherein each of the is an oxygen atom.

3. The resin composition according to claim 1 or 2, wherein the polyimide precursor (A) has a biphenyl structure.

4. The resin composition according to any one of claims 1 to 3, wherein the polyimide precursor (A) contains a polyamic acid ester structure.

5. The polyimide precursor (A) contains 30 mol % or more and 100 mol % or less of the residue of the acid anhydride represented by the formula (1), relative to 100 mol % of all carboxylic acid residues in the polyimide precursor (A). The resin composition according to any one of claims 1 to 4.

6. A cured film obtained by curing the resin composition according to any one of claims 1 to 5.

7. The cured film of claim 6 which is patterned by UV laser ablation.

8. The cured film according to claim 6 or 7, wherein the imidization rate is 97% or more and 100% or less.

9. The cured film according to any one of claims 6 to 8, which is cured at a curing temperature of 200°C to 250°C.

10. A method for producing a pattern of a cured film, comprising the steps of: applying the resin composition according to any one of claims 1 to 5 to a substrate; volatilizing the solvent (B) at 80°C or more and less than 150°C; curing the composition at 150°C or more and 250°C or less; and ablation processing the composition by a UV laser.

11. An electronic part comprising the cured film according to any one of claims 6 to 9.

12. An antenna element comprising at least one antenna wiring and the cured film according to any one of claims 6 to 9, The antenna wiring includes at least one antenna selected from the group consisting of a meandering loop antenna, a coiled loop antenna, a meandering monopole antenna, a meandering dipole antenna, and a microstrip antenna, and the area occupied by each antenna portion in the antenna wiring is 1000 mm 2 The antenna element according to claim 1, wherein the cured film is an insulating film that provides insulation between the ground and the antenna wiring.

13. A semiconductor package including at least a semiconductor element, a rewiring layer, a sealing resin, and an antenna wiring, The antenna wiring includes at least one antenna selected from the group consisting of a meandering loop antenna, a coiled loop antenna, a meandering monopole antenna, a meandering dipole antenna, and a microstrip antenna, and the area occupied by each antenna portion in the antenna wiring is 1000 mm 2 10. A semiconductor package comprising: an insulating layer of a redistribution layer and / or a sealing resin comprising the cured film according to any one of claims 6 to 9; and a sealing resin disposed between a ground and an antenna wiring.

Citation Information

Patent Citations

  • Anisotropic conductive adhesive film

    JP1996176320A

  • Polyimide resin for laser processing and solution composition thereof

    JP2001213962A

  • Photosensitive resin composition, method for manufacturing cured relief pattern, and semiconductor device

    JP2011169980A

  • Base generator, photosensitive resin composition, pattern formation material made of the photosensitive resin composition, method for manufacturing relief pattern and product using the photosensitive resin composition

    JP2011213783A

  • Radical polymerizable polyamide, resin composition, and insulation member

    JP2019119886A